Visual assessment of diffusion weighted imaging infarct volume lacks accuracy and reliability. (2nd February 2019) - Khoury, Naim; Dargazanli, Cyril; Guenego, Adrien; Zuber, Kevin; Ekmen, Asya; Charbonnier, Guillaume; Hebert, Solène; Capron, Jean; Sabben, Candice; Morvan, Erwan; Boisseau, William; Maier, Benjamin; et al.
Abstract : Purpose: The DAWN trial (Diffusion weighted imaging or CT perfusion Assessment with clinical mismatch in the triage of Wake-up and late presenting strokes undergoing Neurointervention with Trevo) has demonstrated the benefits of thrombectomy in patients with unknown or late onset strokes, using automated software (RAPID) for measurement of infarct volume. Because RAPID is not available in all centers, we aimed to assess the accuracy and repeatability of visual infarct volume estimation by clinicians and the consequences for thrombectomy decisions based on the DAWN criteria. Materials and methods: 18 physicians, who routinely depend on MRI for acute stroke imaging, assessed 32 MR scans selected from a prospective databaseover two independent sessions. Raters were asked to visually estimate the diffusion weighted imaging (DWI) infarct volume for each case. Sensitivity, specificity, and accuracy of the estimated volumes were compared with the available RAPID measurements for various volume cut-off points. Thrombectomy decisions based on DAWN criteria with RAPID measurements and raters' visual estimates were compared. Inter-rater and intra-rater agreement was measured using kappa statistics. Results: The mean accuracy of raters was <90% for all volume cut-points. Inter-rater agreement was below substantial for each DWI infarct volume cut-off points. Intra-rater agreement was substantial for 55–83% of raters, depending on the selected cut-off points. Applying DAWN criteria with visual estimates instead of RAPID measurements led to 19% erroneous thrombectomy decisions, and showed a lack of reproducibility. Conclusion: The visual assessment of DWI infarct volume lacks accuracy and repeatability, and could lead to a significant number of erroneous decisions when applying the DAWN criteria.